Differences in pain and function between adolescent athletes and physically active non-athletes with patellofemoral pain - Ferreira, Amanda Schenatto [UNESP]; de Oliveira Silva, Danilo [UNESP]; Priore, Liliam Barbuglio Del [UNESP]; Garcia, Carmen Lucia Gomes [UNESP]; Ducatti, Matheus Henrique Maiolini [UNESP]; Botta, Ana Flavia Balotari [UNESP]; Waiteman, Marina Cabral [UNESP]; de Azevedo, Fábio Mícolis [UNESP] (Elsevier, 2018)
Objectives: To investigate pain level and function limitation in adolescent athletes and physically active non-athletes with PFP. Design: Cross-sectional study. Setting: Adolescent athletes were recruited at a sport center complex. Adolescent non-athletes were recruited from upper secondary schools. Participants: 108 adolescents diagnosed with PFP: 42 adolescent athletes and 66 adolescent non-athletes. Main outcome measures: To evaluate the level of pain, a visual analog scale (VAS) was used and to evaluate the overall function, the Knee Outcome in Osteoarthritis Survey (KOOS) was used. Results: The adolescent athletes scored significantly higher in the VAS (Mean difference = 0.97 (95% CI = 0.35; 1.60) p = 0.003) compared to adolescent non-athletes. Adolescent athletes scored lower in the KOOS - Symptoms, Pain, Knee-related quality of life and Sport and recreation dimensions - than the non-athletes, however, the minimally clinically important difference was not achieved in Pain dimension. There was no significant difference in the Activities of daily living dimension of the KOOS. Conclusions: Adolescent athletes presented higher levels of pain and lower physical function status compared with physically active non-athletes. This provides an important insight to the management of PFP in adolescent athletes as worst functional status is linked with poor prognosis in patients with PFP.
Keywords: Adolescents; Anterior knee pain; Knee; Physical function